The Use of Flashcards to Improve Students’ Vocabulary Achievement - Razaq, Yusuf; Amiruddin, Amiruddin (ETDC: Indonesian Journal of Research and Educational Review, 2022)
This study looked at how flashcards improved students' vocabulary accomplishment in terms of word classes (noun, verb, adjective, adverb), word meaning, and language use in the third semester of English education at IAI As'adiyah Sengkang. A pre-experimental strategy was used in this study. The research sample consisted of 13 pupils. The researcher selected 8.5 as the research sample using a cluster random sampling technique. Data on students' vocabulary achievement was collected using multiple-choice, word meaning, and sentence-making exercises, and then analyzed using SPSS 24. There was a considerable improvement between the pre-test and post-test findings. The students' experimental post-test score of 69.3871 was greater than their pre-test score of 47.2258, demonstrating this. Furthermore, the results revealed that the probability value (0.00) was less than the significance level (0.05). The researcher found that employing flashcards boosted pupils' vocabulary achievement based on the findings.